Platelet cNOS Activity Is Reduced in Patients with IDDM and NIDDM - Martina, Valentino; Bruno, Guido A.; Trucco, Fulvia; Zumpano, Elena; Tagliabue, Milena; Bisceglie, Cataldo Di; Pescarmona, Gianpiero (Thrombosis and Haemostasis, 1998)
Several studies in vitro and in vivo suggest that the nitric oxide (NO) production is impaired in diabetes mellitus. Reduced levels of NO could contribute to vascular alteration facilitating platelet-vascular wall interaction, adhesion of monocytes to endothelium, vascular smooth muscle proliferation and by decreasing endothelium-dependent vasodilation. In this study we evaluated the activity of the constitutive nitric oxide synthase (cNOS) in platelets of patients with insulin-dependent diabetes mellitus (IDDM) and with non-insulin-dependent diabetes mellitus (NIDDM). When compared to that of normal subjects, cNOS activity is significantly lower in patients with IDDM and with NIDDM (1.57 ± 0.25 vs. 0.66 ± 0.10 fmol/min/10 9 PLTs and 1.57 ± 0.25 vs. 0.67 ± 0.08, respectively; p <0.005). These data demonstrate that the platelet cNOS activity is decreased in diabetes mellitus.